DEVELOPMENT OF SELECTION CRITERIA FOR EVALUATION OF HOT PEPPER (CAPSICUM ANNUM L) GENOTYPE RESILIENT TO CLIMATE CHANGE - AMIN, M; SAEED, MS; ABBAS, W; ALI, S; AHMED, I; KHAN, QAT; ULLAH, A; AHMAD, M (Biological and Clinical Sciences Research Journal, 2024)
The hot pepper chilli, scientifically referred to as Capsicum spp., is globally recognized for its extensive use in cooking and industry. However, rising temperatures due to changing climate conditions are impacting crop yields by affecting pollen viability, as well as the setting and size of the fruit. To combat this, fifteen hot pepper genotypes were assessed to determine which one is most resilient to these climatic challenges. The results indicated that the VRIHP006 genotype exhibited the highest fruit setting and pollen viability percentage among the hot pepper genotypes, with an impressive 86% at optimal temperature and 36.4% under elevated temperatures followed by VRIHP001 and VRIHP004. The data of seed No. fruit-1, fruit length (cm), and fruit width (mm) manifested that genotypes that had less impact of temperature on fruit setting and pollen viability also maintained seed No. fruit-1, fruit length (cm) and fruit width. The Heat susceptibility indices also supported the above selection criteria.